Pembrolizumab-induced type-1 diabetes mellitus: clinical characteristics, therapeutic strategies, and prognosis from a retrospective analysis of 43 published cases - Jincai Guo; Yixiang Hu; Ya Liu; Yan Wang (Frontiers in Endocrinology, 2026)
Background Pembrolizumab-induced type 1 diabetes mellitus (T1DM) is an uncommon but potentially life-threatening immune-related adverse event. Its clinical course is often abrupt, and evidence regarding its presentation, management, and long-term outcome remains largely derived from isolated case reports. Methods Published case reports and case series describing pembrolizumab-induced T1DM were retrieved from PubMed, Embase, Web of Science, CNKI, and Wanfang Data from database inception to June 30, 2026, and retrospectively reviewed. Patient demographics, pembrolizumab exposure, clinical manifestations, laboratory findings, treatments, and outcomes were extracted and analyzed descriptively. Results 40 eligible articles identified 43 patients. The median age was 67 years (range, 12–87), and 24 patients (55.8%) were male. The median interval from pembrolizumab initiation to T1DM onset was 15 weeks (range, 3–104). Melanoma (34.9%) and lung cancer (23.3%) were the most common underlying malignancies, and 35 of 42 patients (83.3%) had no pre-existing diabetes. The predominant symptoms were fatigue or malaise (62.5%), polyuria, polydipsia, or thirst (57.5%), and nausea or vomiting (45.0%). Diabetic ketoacidosis occurred in 36 patients (83.7%). The median blood glucose level at presentation was 558 mg/dL (range, 277–1256), and the median HbA1c was 8.3% (range, 4.6–11.4). C-peptide was low in 30 of 34 patients (88.2%), whereas islet autoantibodies were detected in only 15 of 39 patients (38.5%). All patients required insulin therapy, and 27 (62.8%) received fluid or electrolyte replacement. Among 33 patients with available follow-up data, 32 (97.0%) had persistent insulin dependence or β-cell deficiency. Pembrolizumab was continued or restarted in 13 of 33 patients (39.4%); recurrent diabetic ketoacidosis was reported in one of these 13 patients. Conclusion Pembrolizumab-induced T1DM is characterized by rapid and usually irreversible β-cell failure, frequent diabetic ketoacidosis, and persistent insulin dependence. Negative islet autoantibodies do not exclude the diagnosis. Glucose monitoring and prompt assessment of hyperglycemic symptoms are essential during and after treatment.